2002
DOI: 10.1021/jp0146869
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Thermal Decomposition of Alkanethiols on Cu(110)

Abstract: Adsorption and thermal decomposition of alkanethiols (RSH, R ) CH 3 , C 2 H 5 , and C 4 H 9 ) on a Cu(110) surface have been studied by means of temperature-programmed desorption (TPD) and X-ray photoemission spectroscopy (XPS) with synchrotron radiation. At a small coverage, CH 3 SH and C 2 H 5 SH dissociate to form surface thiolates and hydrogen, whereas C 4 H 9 SH adsorbs molecularly on the surface at 100 K; adsorbed C 4 H 9 SH begins to deprotonate at ∼170 K. All of these alkanethiolates can decompose to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
85
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(101 citation statements)
references
References 49 publications
14
85
2
Order By: Relevance
“…Similar dehydrogenations of aliphatic carbon chains were reported for alkanethiols and mercaptanoundecanoic acids where, upon heating to $600 K, all chemisorbed alkanethiols began to produce hydrogen and yield carbon clusters on the surface [28,37,38]. The high temperature peak above 760 K being a result of sample holder degassing can be excluded since we did not observe this peak when performing experiments with a Au(1 1 1) surface that had not been exposed to OTTP.…”
Section: Adsorption and Thermal Decomposition Of Ottp On Ausupporting
confidence: 77%
“…Similar dehydrogenations of aliphatic carbon chains were reported for alkanethiols and mercaptanoundecanoic acids where, upon heating to $600 K, all chemisorbed alkanethiols began to produce hydrogen and yield carbon clusters on the surface [28,37,38]. The high temperature peak above 760 K being a result of sample holder degassing can be excluded since we did not observe this peak when performing experiments with a Au(1 1 1) surface that had not been exposed to OTTP.…”
Section: Adsorption and Thermal Decomposition Of Ottp On Ausupporting
confidence: 77%
“…Through the use of radiolabeled hexadecanethiolate monolayers, the complete loss of surface sulfur at 210°C was observed, with some loss occurring at as low as 100°C [16]. Similarly, Lai et al [17] have reported that the decomposition of alkanethiols (RSH with R=CH 3 , C 2 H 5 , and C 4 H 9 ) on a Cu (110) surface reaches a maximum rate at 70°C. They also reported that the same alkanethiols, when adsorbed on a Pt(111) surface, also decomposed at a temperature below 100°C [18].…”
Section: Experimental: Materials and Methodsmentioning
confidence: 88%
“…Studies of x-ray photoelectron spectroscopy have shown that C 2 H 5 SH decomposes to form C 2 H 5 S-on Cu(1 1 1) at 85 K and on Cu(1 1 0) at 100 K at lower coverages [5,11]. In Fig.…”
Section: Vibrational Studies Of Thermal Decomposition Of Hsch 2 Ch 2 Ohmentioning
confidence: 94%
“…However, as the surface is precovered with oxygen, C 2 H 5 OH deprotonates readily to form an ethoxide at 200-300 K [4]. C 2 H 5 SH dissociates on Cu(1 1 0) to form an ethyl thiolate at $100 K [5]. In the present study, thermal decomposition of HSCH 2 CH 2 OH at coverages below half the monolayer on Cu(1 0 0) is investigated by temperature-programmed reaction/desorption (TPR/D) and reflection-absorption infrared spectroscopy (RAIRS).…”
Section: Introductionmentioning
confidence: 99%